Qualidade de vida no trabalho de pessoas com deficiência - Oliveira, Elisangela de Castro Freitas (2013)
The research theme is the Quality of Working Life – QWL for People with Disabilities – PCD. This issue is relevant for consideration of possible insertion and maintenance of these workers in the labor market, promoting an environment conducive to the development of personal and professional skills. The research aims to analyze the QWT of PCD based upon the relationship between QWL studies and professional factors in a higher education institution. The study aims to identify factors QWT, with reference to the theoretical model of Walton; identify factors of professional reference to the IMBA model, relate and analyze studies with QWL factors IMBA professional model. The adopted methodological approach was qualitative, through interview. Data analysis was performed using the technique of content analysis by Bardin. The results refer to a certain degree in the lack of QWL in the researched group. The factors remuneration and working conditions were highlighted as the most relevant. Professional development, professional growth and stability in the institution and the balance between work and personal life factors were pointed with a median level of importance; social integration in the institution, the institution tights and the meaning of the enterprise in local community were presented as the factors that less interfere in the maintenance QWL. Concerning the factors of the professional capacity in the model IMBA, the group presented partial compatibility between professional and work demands. Among the twenty-four factors, only four of them correspond to work demands and professional abilities, namely attention in the workplace, agility at work; personal capacity to take decisions at work and communication skills with customers. The instruments used in this study (QWL factors and professional Capacity Factors Model IMBA) have been effective for the achievement the of established objectives and contributed to the understanding of the theme as well as, and may be useful for application in other researches and practices in the field of Organizational Psychology.